Rainfall interception loss by Cupressus arizonica and Pinus eldarica in an arid zone afforestaion of Iran (Biyarjomand, Shahroud) - Hoseyn Bagheri; Pedram Attarod; Vaheid Etemad; Heydar Sharafieh; Mohammad Taghi Ahmadi; Mohsen Bagheri (تحقیقات جنگل و صنوبر ایران, 2011)
The main aim of the present research was to measure interception (I) by individual trees of Pinus eldarica and Cupressus arizonica that extensively planted in afforestation projects of the arid zone in Iran. The selected trees were located inside a forest plantation in a dry area at Semnan province, where mean annual precipitation and air temperature are 127 mm and 16˚C, respectively. The gross rainfall (GR) was measured by the mean of three hand-made gauges placed in an open area neighboring to the chosen trees. Five individual trees were selected for measurements of throughfall (TF). Eight TF collectors were positioned beneath the tree canopies in the four main directions to average into TF mean per species. I was calculated as the difference between GR and TF for each tree and I was finally averaged into the means of P. eldarica and C. arizonica. Measurements were made on a rainfall event basis during 2009 summer season, from March to October. The cumulative GR depth of 12 events was 37.9 mm; I (P. eldarica): 17.2 mm, and I (C. arizonica):12.3 mm. On the event scale average ratios of I:GR were 68% (1.4 mm per event) and 55% (1 mm per event) for P.eldarica and C.arizonica, respectively. Strong positive correlations were observed between I and GR (P.eldarica, R2=0.94; C.arizonica, R2=0.87). Our measurements suggested that intercepted GR or I:GR ratio by the canopies, and loss through evaporation decreased, as the size of rainfall events increased. The results showed that interception is a significant component of the seasonal water balance in the afforestation of the arid zone of Iran.